Acts - Garland, David E.; Strauss, Mark L., 1959-; Walton, John H., 1952-; Harney, Kevin; Harney, Sherry, 1960-; Barr, Adam T. (Grand Rapids, Michigan : Baker Books, 2017)
"The book of Acts is theological history, showing how Jesus's crucifixion and resurrection informed the life, teaching, and ministry of the early church. God's power is displayed through the Spirit in the outward spread and influence of the gospel. We see how God's Old Testament promises are fulfilled in the church, composed of both Jews and Gentiles. It is an open-ended story, so its history and theology are needed for the life and mission of the church today." -- !c From publisher's description.
Introduction to Acts -- Acts 1:1-11: Jesus' Resurrection and Ascension: The Continuation of the Story -- Acts 1:12-26: Replacing Judas among the Twelve -- Acts 2:1-13: The Coming of the Spirit -- Acts 2:14-47: The Spirit Inspires the Bold -- Proclamation of the Gospel -- Acts 3:1-26: The Healing of a Lame Man at the Temple Gates -- Acts 4:1-31: The Apostles Bold under Fire and the Church Fervent in Prayer -- Acts 4:32-5:11: God Giving and Deadly Lies: Barnabas and Ananias and Sapphira -- Acts 5:12-42: Signs, and Wonders, and Persecution -- Acts 6:1-7: The Appointment of the Seven -- Acts 6:8-7:50: Stephen's Arrest and Speech -- Acts 7:51-8:3: Stephen's Martyrdom -- Acts 8:4-25: The Extension of the Mission in Samaria -- Acts 8:26-40: Philip and the Ethiopian -- Acts 9:1-30: Saul's Conversion and Call -- Acts 9:31043: Peter's Ministry in Lydda and Joppa: Healing Aeneas and raising Tabitha -- Acts 10:1-48: The Apostle Peter and the Centurion Cornelius -- Acts 11:1-18: Peter's Report to Jerusalem Believers -- Acts 11:19-30: Solidarity between Two Christian Communities -- Acts 12:1-25: James's Death, Peter's Escape, and Herod's Demise -- Acts 13:1-12: Resistance, and Success in Cyprus -- Acts 13:13-52: The Expansion of the Gospel in Pisidian Antioch -- Acts 14:1-28: Ministry in Iconium, Lystra, and Derbe -- Acts 15:1-35: The Jerusalem Council: What Is to Be Required of Gentile Converts? -- Acts 15:36-16:15: Paul and Barnabas Split Up, but the Mission Continues -- Acts 16:16-40: Rocking the Jailhouse -- Acts 17:1-15: Rejection in Thessalonica and Acceptance in Berea -- Acts 17:16-34: Paul's Defense before the Areopagus Council -- Acts 18:1-17: Law and Disorder in Corinth -- Acts 18:18-19:7: Believers Are Strengthened, and Jews are Presented with Persuasive Arguments That Jesus is the Messiah -- Acts 19:8-41: The Clash of Gods: Making Waves in a world of Rival Religiosity -- Acts 20:1-16: Paul Brings Renewal to the churches -- Acts 20:17-38: Paul's Bittersweet Farewell Exhortation at Miletus -- Acts 21:1-14: Prepared to Die for the Name of the Lord Jesus -- Acts 21:15-26: Paul Meets James and the Elders in Jerusalem -- Acts 21:27-40: Paul's Arrest in the Temple -- Acts 22:1-30: Paul's Defense in the Temple -- Acts 23:1-10: Paul's Defense before the Sanhedrin -- Acts 23:11-35: The Vison of God's Purpose for Paul and the Plot against His Life -- Acts 24:1-27: The Hearing before Governor Felix in Caesarea -- Acts 26:1-32: Paul's Speech before King Agrippa -- Acts 27:1-28:10: Storm, Shipwreck, and Shelter -- Acts 28:11-31: The Chained Paul and the Unhindered Gospel
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries